2007
DOI: 10.1002/gps.1816
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of amnestic Mild Cognitive Impairment to dementia of Alzheimer type is independent to memory deterioration

Abstract: In subjects with aMCI poor global cognitive performance at baseline, the worsening on executive functions and on functional status but not the worsening on memory functions are independently associated with the conversion to dementia of Alzheimer type at 1 year, follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 37 publications
10
116
1
4
Order By: Relevance
“…Any NPS: Three small clinical studies found NPI total scores were not associated with risk of conversion from any type MCI to all cause dementia 42;43 or aMCI to AD 44 (pooled effect size 0.0, -0.39 to 0.40). A higher quality epidemiological study also found no association of total Neuropsychiatric Inventory (NPI) score with conversion from any type MCI to all cause dementia, after controlling for age and education 45 , while one small additional clinical study found that it did predict conversion from any type MCI to AD 46 .…”
Section: Neuropsychiatric Symptoms (Nps)mentioning
confidence: 99%
“…Any NPS: Three small clinical studies found NPI total scores were not associated with risk of conversion from any type MCI to all cause dementia 42;43 or aMCI to AD 44 (pooled effect size 0.0, -0.39 to 0.40). A higher quality epidemiological study also found no association of total Neuropsychiatric Inventory (NPI) score with conversion from any type MCI to all cause dementia, after controlling for age and education 45 , while one small additional clinical study found that it did predict conversion from any type MCI to AD 46 .…”
Section: Neuropsychiatric Symptoms (Nps)mentioning
confidence: 99%
“…Pathologically, MCI brain shows mild degradation of the hippocampus, entorhinal cortex, sulci, and gyri as evaluated by using magnetic resonance imaging (MRI) technology (54), while early and late stage AD patients have considerably greater degradation in these areas (61). It is estimated that the rate of conversion of amnestic MCI to AD is roughly 10%-15% per year (173); however, in some cases individuals with MCI can revert to normal (153).…”
Section: G93amentioning
confidence: 99%
“…57 It is interesting to note that worsening of memory impairment was not shown to be a major predictor of MCI conversion in a large longitudinal study. 58 In this study, the emergence of executive dysfunction during follow-up was the most important determinant of conversion from MCI to AD. This finding highlights the importance of careful assessment of other cognitive domains beyond memory in these individuals.…”
Section: Longitudinal Studies and MCI Prognosismentioning
confidence: 99%